(untitled) (UTM Press - Edited Book, 2025)
In a world racing toward sustainable development, this book offers an insightful journey through the frontiers of energy and materials innovation. Tackling critical issues from biofuel simulation to GHG emission tracking and nuclear fuel optimization, each chapter delivers practical, research-based solutions for real-world sustainability challenges. Designed to spark action and foster understanding, this volume equips students, researchers, and industry professionals with the knowledge to drive green transitions in engineering. With a compelling blend of theory, technology, and application, the book serves as both a resource and a catalyst empowering the reader to contribute to a cleaner, smarter, and more resilient energy future.